Bacterial Composition Associated With Giant Colonies of the Harmful Algal Species Phaeocystis globosa - Zhu, Zhu; Meng, Rui; Smith Jr., Walker O.; Doan-Nhu, Hai; Nguyen-Ngoc, Lam; Jiang, Xinjun (Frontiers in Microbiology, 2021)
The cosmopolitan algae Phaeocystis globosa forms harmful algal blooms frequently in a number of tropical and subtropical coastal regions in the past two decades. During the bloom, the giant colony, which is formed by P. globosa, is the dominant morphotype. However, the microenvironment and the microbial composition in the intracolonial fluid is poorly understood. Here, we used high-throughput 16S rRNA amplicon sequencing to examine the bacterial composition and predicted functions in intracolonial fluid. Compared with the bacterial consortia in ambient seawater, intracolonial fluids possessed the lower levels of microbial richness and diversity, implying selectivity of bacteria by the unique intracolonial microenvironment enclosed within the P. globosa polysaccharide envelope. The bacterial consortia in intracolonial fluid were dominated by Balneola (48.6% of total abundance) and Labrezia (28.5%). The bacteria and microbial function enriched in intracolonial fluid were involved in aromatic benzenoid compounds degradation, DMSP and DMS production and consumption, and antibacterial compounds synthesis. We suggest that the P. globosa colonial envelope allows for the formation of a specific microenvironment; thus, the unique microbial consortia inhabiting intracolonial fluid has close interaction with P. globosa cells, which may benefit colony development.